Anti-glutathione S-transferase theta 1 antibodies correlate with graft loss in non-sensitized pediatric kidney recipients - Patrizia Comoli; Michela Cioni; Bryan Ray; Augusto Tagliamacco; Annalisa Innocente; Gianluca Caridi; Maurizio Bruschi; Jayasree Hariharan; Iris Fontana; Antonella Trivelli; Alberto Magnasco; Angela Nocco; et al. (Frontiers in Medicine, 2022)
IntroductionImmunity to Human leukocyte antigen (HLA) cannot explain all cases of ABMR, nor the differences observed in the outcome of kidney recipients with circulating DSAs endowed with similar biologic characteristics. Thus, increasing attention has recently been focused on the role of immunity to non-HLA antigenic targets.MethodsWe analyzed humoral auto- and alloimmune responses to the non-HLA antigen glutathione S-transferase theta 1 (GSTT1), along with development of de novo (dn)HLA-DSAs, in a cohort of 146 pediatric non-sensitized recipients of first kidney allograft, to analyze its role in ABMR and graft loss. A multiplex bead assay was employed to assess GSTT1 antibodies (Abs).ResultsWe observed development of GSTT1 Abs in 71 recipients after transplantation, 16 with MFI > 8031 (4th quartile: Q4 group). In univariate analyses, we found an association between Q4-GSTT1Abs and ABMR and graft loss, suggesting a potential role in inducing graft damage, as GSTT1 Abs were identified within ABMR biopsies of patients with graft function deterioration in the absence of concomitant intragraft HLA-DSAs. HLA-DSAs and GSTT1 Abs were independent predictors of graft loss in our cohort. As GSTT1 Ab development preceded or coincided with the appearance of dnHLA-DSAs, we tested and found that a model with the two combined parameters proved more fit to classify patients at risk of graft loss.DiscussionOur observations on the harmful effects of GSTT1Abs, alone or in combination with HLA-DSAs, add to the evidence pointing to a negative role of allo- and auto-non-HLA Abs on kidney graft outcome.